Possibility to use solar induced ventilation strategies in tropical conditions by computational fluid dynamic simulation - Nugroho, Agung Murti; Ahmad, Mohd. Hamdan (2005)
The climatic conditions of the tropical regions are characterized by high air temperatures, high relative humidity's and very low wind speeds, which make the environmental conditions uncomfortable. The use of solar roof chimneys in buildings is one way to increase natural ventilation and, as a consequence, improve indoor air quality. The present study evaluates the stack induced ventilation strategies performance on experimental room model in Malaysian condition. The use of solar induced ventilation strategies in building was investigated using CFD FloVent technique. Validation of CFD Flovent was done by comparing the pilot testing. The effect of solar chimney, solar wall, and solar roof were simulated in order to determine the best option for a tropical ventilation strategy. The simulations were performed on selected model of trombe wall, solar chimney, and solar roof. The results showed the solar chimney can increase air velocity in the room but also increase heat gain in the room. The results also indicated that solar roof reduced the heat gain but resulted in low air velocity. Use of solar wall can increase air velocity in the room depending on the orientation of the solar wall. Based on the above finding a combined strategy was developed to increase stack induced ventilation.